2014
DOI: 10.1111/jeb.12385
|View full text |Cite
|
Sign up to set email alerts
|

Dioecy is associated with higher diversification rates in flowering plants

Abstract: In angiosperms, dioecious clades tend to have fewer species than their nondioecious sister clades. This departure from the expected equal species richness in the standard sister clade test has been interpreted as implying that dioecious clades diversify less and has initiated a series of studies suggesting that dioecy might be an 'evolutionary dead end'. However, two of us recently showed that the 'equal species richness' null hypothesis is not valid in the case of derived char acters, such as dioecy, and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 84 publications
(151 reference statements)
1
51
1
1
Order By: Relevance
“…In addition, comparative genomic studies of sterilizing and nonsterilizing mitochondrial genomes that co-occur in a given species have shown that sterilizing genomes exhibit a higher rate of evolution (Darracq et al 2010(Darracq et al , 2011. As dioecy and sex-chromosomes have been suggested to drive speciation rates (Käfer et al 2014;Graves 2016), gynodioecy could reveal itself to be another reproductive system that facilitates reproductive isolation and thus speciation in a very effective way, in a tempo faster than phenotypic diversification (Orr 1995), resulting in cryptic species. Therefore, we expect that the accumulation of mutations in the mitochondrial genome occurs independently in the two S. nutans lineages and would ultimately induce reproductive isolation through cytonuclear genetic incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comparative genomic studies of sterilizing and nonsterilizing mitochondrial genomes that co-occur in a given species have shown that sterilizing genomes exhibit a higher rate of evolution (Darracq et al 2010(Darracq et al , 2011. As dioecy and sex-chromosomes have been suggested to drive speciation rates (Käfer et al 2014;Graves 2016), gynodioecy could reveal itself to be another reproductive system that facilitates reproductive isolation and thus speciation in a very effective way, in a tempo faster than phenotypic diversification (Orr 1995), resulting in cryptic species. Therefore, we expect that the accumulation of mutations in the mitochondrial genome occurs independently in the two S. nutans lineages and would ultimately induce reproductive isolation through cytonuclear genetic incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual system has, however, been investigated as a possible correlate of lineage diversification rate (Heilbuth 2000;Kay et al 2006;Käfer et al 2014;Sabath et al 2016). Sexual system has, however, been investigated as a possible correlate of lineage diversification rate (Heilbuth 2000;Kay et al 2006;Käfer et al 2014;Sabath et al 2016).…”
Section: Phylogenetic Modelsmentioning
confidence: 99%
“…Sexual system is a key determinant of genetic variation and reproductive success, affecting evolutionary processes within populations (Bawa 1980;Charlesworth and Wright 2001;Eppley and Pannell 2007;Queenborough et al 2009) and potentially the origination and extinction of species (Vamosi and Vamosi 2005;Kay et al 2006;Käfer et al 2014;Sabath et al 2016). Sexual system is a key determinant of genetic variation and reproductive success, affecting evolutionary processes within populations (Bawa 1980;Charlesworth and Wright 2001;Eppley and Pannell 2007;Queenborough et al 2009) and potentially the origination and extinction of species (Vamosi and Vamosi 2005;Kay et al 2006;Käfer et al 2014;Sabath et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, building upon an improved test for sister clade comparisons (Käfer & Mousset ), Käfer et al . () documented a small positive effect of dioecy on species richness, suggesting that diversification might be more rapid in at least some of the dioecious lineages than in the hermaphrodite lineages from which they are derived. Second, using recently developed phylogenetic tools (Maddison et al .…”
Section: Introductionmentioning
confidence: 99%